A case study on an explosion accident of a 110 kV porcelain housed MOA. (September 2020) - Li, Qian; Zhou, Zikai; Zhou, Wenqing; Wei, Juntao; Wang, Kai; Liu, Gang; Deng, Honglei; Wang, Peng; Shu, Jian
Highlights: It was considered that the high temperature and high humidity environment in coastal areas were related to the increase of leakage current of MOA in long-term operation. An electrothermal model of MOA was established to analyse the influence of the formation of dry zone on the heating of varistors. The pollution formation and cleaning process, which was caused by salt spray deposition and precipitation erosion in coastal areas, may accelerate the degradation of the side insulation glaze of the varistor. Abstract: A metal oxide arrester (MOA) accident occurred in a tropical coastal area is studied in this paper. The control test and disassembly analysis for the MOAs in the accident group and the control group were conducted. It was considered that the varistors of the MOA were deteriorating. Although the performance of the zinc oxide (ZnO) varistor is qualified, its side insulation glaze has defects. The leakage current under U1mA and 0.75 U1mA have exceeded the standard requirements due to the decrease of insulation performance. An electrothermal model of the MOA was constructed. The root-mean-square (RMS) value of the voltage across the varistor column and the RMS of leakage current flowing through the varistor were obtained through simulation. The heating power was calculated as the heat source input of the thermal circuit model to calculate the temperature of the varistor. It was verified that the electrolyte deposited on the surface of the porcelain house due to salt spray formed a dry area after being affected by moisture, because of the uneven potential distribution, the radial current flowing to the varistors through the coupling capacitor on the surface of the porcelain house increased sharply, and it caused the varistor to generate a large amount of heat in extreme condition. The side insulation glaze of the varistor was damaged by frequent heating effect. Eventually, the internal flashover occurred in the MOA, and the internal pressure rose sharply then broke through the explosion-proof film, causing an accident.